2005
DOI: 10.1007/s10630-005-0034-9
|View full text |Cite
|
Sign up to set email alerts
|

Postradiation immunosuppressive and attractive volatile secretions: The “baystander effect” or allelopathy in groups of animals

Abstract: It was shown earlier that mice or rats exposed to sublethal doses of ionizing radiation are able to decrease the immune reactivity of intact animals when kept together with them in the same cage for 10-15 days [1]. The same effect was observed in the presence of urine of irradiated animals, when a sheet of paper that for one day adsorbed urine of irradiated animals was placed in a cage with intact animals [2,3]. In both cases, the content of antibody-forming cells (AFCs) induced with sheep erythrocytes ( 1 × 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 6 publications
1
17
0
Order By: Relevance
“…There has been only a scarce amount of studies on radiation induced bystander effect (RIBE) on the interorganism level including the study on RIBE between mice by Surinov et al, 2 and study on RIBE between whole fish by Mothersill's group 4,5 as described in the Introduction. The first part of the present study demonstrated the successful induction of the bystander effect in 10 naive embryos by partnering them with the 50 irradiated embryos (irradiated with 4 Gy of X-rays at 5 hpf) in the same medium immediately after irradiation until 25 hpf.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been only a scarce amount of studies on radiation induced bystander effect (RIBE) on the interorganism level including the study on RIBE between mice by Surinov et al, 2 and study on RIBE between whole fish by Mothersill's group 4,5 as described in the Introduction. The first part of the present study demonstrated the successful induction of the bystander effect in 10 naive embryos by partnering them with the 50 irradiated embryos (irradiated with 4 Gy of X-rays at 5 hpf) in the same medium immediately after irradiation until 25 hpf.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Surinov et al 2 reported RIBE between mice and revealed that the bystander signal was transmitted through urine. RIBE has also been shown to occur between fish.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It would also be interesting and beneficial to study whether the CF can be transmitted at the inter-organismic level. Recently, there has been massive evidence of the RIBE occurring at the inter-organismic level, e.g., between mice [50,51], zebrafish [52] and medaka [53].…”
Section: Definition and History Of The Ribementioning
confidence: 99%
“…Th ese eff ects have also been related to RIBE (Surinov et al 2005). Th erefore, the authors suggest that the cause of the marked error bars may be related to the amount of urine that the bladders were holding at the moment of culturing tissue explants or it may also be individual variation in the reporter cell response.…”
Section: Bystander Eff Ects In Rats After Synchrotron Microbeam Radiamentioning
confidence: 99%